Lighting design method of a football stadium considering visualization - Hyok-Chol U (Talenta Publisher, 2024)
This research is about implementation of visualization to evaluate and correct lighting state and characteristics of lighting engineering on computers in lighting design of football pitch considering shelter and tower. The visualization of architectural lighting and ornament with lamplights designs has not been studied in detail until now in the world, and the method of visualization design for achieving FIFA standards in asymmetric four-tower football stadium lighting is described in the light mode and under the brief introduction by the lighting simulation programs DIALux and Relux..